Factors Affecting the Completion of Follow-Up On Audit Results In Regional Equipment Organizations in South Buton District - Tarfin, Ruslan; Kadir, Abd. Rahman; Sabir, Sabir (Pancasila International Journal of Applied Social Science, 2023)
Communication is a crucial process for information exchange between parties acting as senders and recipients through various media. Competency of Human Resources (HR) is essential for successful company operations, and improving it contributes to effective follow-ups on examination results. This study employs a quantitative descriptive method to examine the influence of communication, HR competency, and disposition on Follow-Up Examination Results (TLHP) in South Buton Regency's Regional Apparatus Organization (OPD) with unfinished audit recommendations. The research involves 100 civil servants as the sample and utilizes primary and secondary data collected through interviews, observations, and document analysis. Multiple regression analysis using SPSS software reveals the significant impact of communication and competency on TLHP. Communication has a positive influence (p-value = 0.002, t = 3.294), while competency positively affects TLHP (p-value = 0.002, t = 3.181). However, disposition shows no significant effect (p-value = 0.807, t = 0.245) on TLHP. The coefficient of determination (R2) at 0.503 indicates that 50.3% of TLHP is explained by these variables. Therefore, this study enhances understanding of the factors influencing TLHP and contributes to local government accountability. In summary, this research emphasizes the significant impact of communication and competency on the effective resolution of Follow-Up Examination Results (TLHP) in the context of the studied organization. However, disposition does not exhibit a substantial influence on TLHP. These findings offer valuable insights for TLHP management, suggesting avenues for organizations to enhance their resolution efficiency.